Breves considerações sobre o conceito de natureza na genese da geografia moderna - Silva, Evandro Soares da [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
From the twentieth century is witnessing a gradual increase in the debates and issues related to the degradation of nature, making the twenty-first century begins under the aegis of speeches linked to this concept as one of the axes of the concerns of humanity. There are several movements that are related to the degrading way of contemporary society and how we are called upon daily to save and defend nature, from the consumption of sustainable products through environmentally friendly lifestyles. While this may appear to be explicit that the current form of metabolic interaction man / nature in the current historical period of capitalism converges in a bleak scenario, however, there is an ideological and peacemaker convergence between productively and the systematic appeal to the consumption. Given these assumptions could be palpable the question that in the course of human history would be ideological conceptions of nature? Being a true statement what is the conflict present in the ideological struggle over nature with regard to the genesis of modern geography? Would it be overt or covert? These questions lead us to the present study, whose goal is to bring some notes about the ideological conceptions of the nature in human history, culminating in the possible influences upon the institutionalization of Modern Geography

A partir do século XX presencia-se um gradativo aumento dos debates e questões ligadas à degradação da “natureza”, fazendo com que o século XXI se inicie sob a égide de discursos atrelados a esse conceito como um dos eixos das preocupações da humanidade. Vários são os movimentos que nos remetem ao caráter degradador da sociedade atual e como somos chamados cotidianamente a “salvar e defender a natureza”, desde o consumo de produtos sustentáveis passando por modelos de vida ecologicamente correto. Mesmo parecendo ser explícito que a atual forma de interação metabólica homem/natureza no atual período histórico do capitalismo converge em um cenário nada promissor, no entanto, verifica-se uma ideológica convergência pacificadora entre a forma produtiva e o apelo sistemático ao consumo. Diante dessas premissas poderia ser palpável a indagação que, no decurso da história da humanidade haveria concepções ideológicas da natureza? Sendo a afirmativa verdadeira qual seria a conflitualidade presente no embate ideológico sobre a natureza quando da gênese da geografia moderna? Seria ela aberta ou velada?Essas indagações nos levam ao presente trabalho, cujo objetivo é trazer alguns apontamentos acerca das concepções ideológicas sobre a natureza na história da humanidade, culminando nas possíveis influências quando da institucionalização da Geografia Moderna
Keywords: Ciencia - Historia; Geografia humana; Natureza; Natureza - Influência do homem; Geografia - Historia; Ontologia; Science - History; Nature; Human geography; Geography - History; Ontology